Does the proposed dividends tax overcome the international tax flaws that secondary tax on companies may have, namely exclusion from the scope of some double tax agreements and violation of the anti-discrimination provisions embodied in the OECD mode - Lovely, Graham (Department of Commercial Law, 2015)
Includes bibliographical references (leaves 54-55).